IMPLEMENTASI EDUKASI PERAWATAN MULUT PADA PASIEN KEMOTERAPI - Pitri, Angela Dwi; Sius, Usu; Listavia Panggus, Florida; Julianti, Na Omi (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Chemotherapy is a common therapeutic modality for cancer patients that may lead to various side effects, including oral mucositis, which can cause pain, impaired eating ability, and decreased quality of life. Preventive strategies, such as oral care education, are essential to minimize these complications. Objective: To evaluate the implementation of oral care education in preventing oral mucositis among chemotherapy patients. Methods: This study employed a qualitative approach with a case study design involving two chemotherapy patients selected through purposive sampling. Data were collected through observation, interviews, and documentation over a seven-day period. Oral mucosal conditions were assessed using the WHO Oral Mucositis Scale. Data analysis was conducted using Colaizzi’s method. Results: After the implementation of oral care education, both patients maintained moist oral mucosa without lesions, pain, or signs of infection. Additionally, patients demonstrated improved understanding and independent behaviors in maintaining oral hygiene. Conclusion: Oral care education is beneficial in preventing oral mucositis and improving patient comfort during chemotherapy. It should be incorporated as a routine nursing intervention for chemotherapy patients.